1995
DOI: 10.1089/neu.1995.12.245
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Effect of Postinjury Treatment with Methylprednisolone or Tirilazad Mesylate on the Increase in Eicosanoid Levels in the Acutely Injured Cat Spinal Cord

Abstract: Methylprednisolone (MP) improves motor recovery in spinal cord-injured patients when administered in a 24 h intensive high dose regimen beginning within 8 h after spinal cord injury (SCI). The rationale for this regimen has been based upon the need for high doses (i.e., 30 mg/kg initial IV dose) to inhibit posttraumatic lipid peroxidation (LP) in the injured spinal segment. However, injury also triggers the immediate calcium-mediated activation of phospholipase A2 (PLA2), the release of arachidonic acid, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…In contrast, and in keeping with our findings, Hall et al 25 reported that methylprednisolone (30 mg/kg) administered 30 min after injury had no effect on eicosanoid (PGE 2 , PGF 2 , 6-keto-PGF 2a , thromboxane B 2 ) concentrations in cat spinal tissue when measured at a single time point 1 h after injury. Thus, the data would suggest that methylprednisolone can reduce generation of PGE 2 after spinal cord injury, but only if given before or immediately after injury occurs.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, and in keeping with our findings, Hall et al 25 reported that methylprednisolone (30 mg/kg) administered 30 min after injury had no effect on eicosanoid (PGE 2 , PGF 2 , 6-keto-PGF 2a , thromboxane B 2 ) concentrations in cat spinal tissue when measured at a single time point 1 h after injury. Thus, the data would suggest that methylprednisolone can reduce generation of PGE 2 after spinal cord injury, but only if given before or immediately after injury occurs.…”
Section: Discussionsupporting
confidence: 91%
“…Hall and his co-workers stated that the doses of MP required for neuroprotection were closer to those needed to inhibit lipid peroxidation and greatly exceeded those required to activate GR (Hall, 1992;Hall, 1993;Hall and Braughler, 1993). MP or 21-aminosteroid is regarded to be effective chiefly as an antioxidant (Hall et al, 1995). On the other hand, the glucocorticoid effects have been recently demonstrated which are independent of the antioxidant effect such as suppressing tumor necrosis factor a (TNFa) expression and NF-kB activation (Hall, 1993;Xu et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Secondary injuries may be triggered during ischemia or trauma by a variety of stimuli, including the formation of reactive oxygen species, lipid peroxidation, excitatory amino acids (25), and a variety of Ca2+-mediated intracellular processes activated by increased Ca +2 influx (26,27). The immune response has also been suggested to be a major contributor to long-term secondary changes.…”
mentioning
confidence: 99%